2007
DOI: 10.1029/2006jd007691
|View full text |Cite
|
Sign up to set email alerts
|

An up‐to‐date quality‐controlled surface mass balance data set for the 90°–180°E Antarctica sector and 1950–2005 period

Abstract: [1] On the basis of thousands of surface mass balance (SMB) field measurements over the entire Antarctic ice sheet it is currently estimated that more than 2 Gt of ice accumulate each year at the surface of Antarctica. However, these estimates suffer from large uncertainties. Various problems affect Antarctic SMB measurements, in particular, limited or unwarranted spatial and temporal representativeness, measurement inaccuracy, and lack of quality control. We define quality criteria on the basis of (1) an up-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(108 citation statements)
references
References 85 publications
(146 reference statements)
9
99
0
Order By: Relevance
“…10, Hg tot concentrations increased between 600-800 and 1000-1100 km from DC in areas characterized by steeper slopes and higher snow accumulation values. Several studies reported a gradual increase in snow accumulation from DC toward the coast (Magand et al, 2007;Verfaillie et al, 2012;Favier et al, 2013), in good agreement with a gradual increase in humidity (Bromwich et al, 2004). These results suggest that the wet deposition of Hg(II) species was enhanced near the coast, resulting in elevated Hg tot concentrations in surface snow samples.…”
Section: Transect From Central To Coastal Antarcticasupporting
confidence: 74%
“…10, Hg tot concentrations increased between 600-800 and 1000-1100 km from DC in areas characterized by steeper slopes and higher snow accumulation values. Several studies reported a gradual increase in snow accumulation from DC toward the coast (Magand et al, 2007;Verfaillie et al, 2012;Favier et al, 2013), in good agreement with a gradual increase in humidity (Bromwich et al, 2004). These results suggest that the wet deposition of Hg(II) species was enhanced near the coast, resulting in elevated Hg tot concentrations in surface snow samples.…”
Section: Transect From Central To Coastal Antarcticasupporting
confidence: 74%
“…As a result, unlike Arthern et al (2006), their method does not introduce local biases due to old measurements made in our study region. This points to the biases introduced by doubtful measurements in SMB extra-and interpolations, and confirms the need for data quality control, such as proposed by Magand et al (2007).…”
Section: Spatial Variations In Accumulationsupporting
confidence: 71%
“…Quality-controlled and updated SMB observations (referred as M07) (Magand et al, 2007) confirm the good accuracy of A06's map in ever-dry-snow region as on the Antarctic Plateau (Sect. 3.1) but also show the negative impact of surface melting (Sect.…”
Section: Introductionmentioning
confidence: 63%
“…Recently, (Magand et al, 2007) produced a qualitycontrolled dataset of SMB measurements by discarding SMB measurements which do not fit quality criteria based on 1) an up-to-date review and quality rating of various SMB measurement methods and 2) coherency, completion, or lack of meta-information (location, date of measurement, time period covered by the SMB values, primary data sources) related to each SMB record. The filtering procedure was applied on V99's dataset (the same data are also in A06) in (Fig.…”
Section: Selection Of Observed Smb Data In 90mentioning
confidence: 99%